Pengaruh Penggunaan Metode Merangkum terhadap Keterampilan Menyimak Siswa Kelas 4 pada Pembelajaran Bahasa Indonesia di MIS Al-Hafza Islamic Global School - Rambe, Riris Nurkholidah; Hafza, Abyena; Juliani, Afrida; Adeana, Fadillah Putri; Harahap, Hasima; Rizky, Putri (Lembaga Yasin AlSys, 2023)
This study aims (1) to find out the reality of the use of the storytelling method in the summarizing method at MIS AL HAFZA ISLAMIC GLOBAL SCHOOL. (2) to find out the reality of students' listening skills using the summarizing method at MIS AL HAFZA ISLAMIC GLOBAL SCHOOL. (3) to find out how much influence the use of the summary method has on students' listening skills. The formulation of the research problems are (1) How is the reality of using the summarizing method at MIS AL HAFZA ISLAMIC GLOBAL SCHOOL? (2) How is the reality of students' listening skills using the summarizing method at MIS AL HAFZA ISLAMIC GLOBAL SCHOOL? (3) How much influence does the use of the summarizing method have on students' listening skills? The research method used is descriptive analysis method which is expressed by a comparison between data or facts in the field with the relevant theoretical basis. The research subjects were 23 students at MIS AL HAFZA ISLAMIC GLOBAL SCHOOL. The results showed that when the pretest in class with the summarizing method went very well and the control class used very high conventional learning.